CSI, crime scene investigation. The complete ninth season [videorecording (DVD)] - Fishburne, Laurence, III, 1961-; Petersen, William L., 1953-; Helgenberger, Marg; Dourdan, Gary; Eads, George, 1967-; Szmanda, Eric; Guilfoyle, Paul (Paramount, 2009)
In the city of Las Vegas, Nevada, with its constant influx of visitors, criminals are provided with ripe targets of all varieties. Luckily for the victims, the Las Vegas Police Department's night shift Crime Scene Investigations is on the case. In this season, Laurence Fishburne joins the CSI team in the lead role of Dr. Raymond Langston.